Integrins in Cancer Treatment - Eble, Johannes A.; Haier, Jorg (Current Cancer Drug Targets, 2006)
Anchorage-independent growth, anoikis resistance, and most steps of metastasis formation are integrin-mediated or -dependent processes, which are characteristics of malignant tumor cells. Acting as oncogenes or tumor suppressor genes, integrins may be involved in the oncogenic transformation of normal cells and their growth into a primary tumor node. During tumorigenesis, a switch of integrin expression can be observed, inasmuch as growth-promoting and growth-attenuating integrins are up- and down-regulated, respectively. ECM-ligand binding to an integrin initiates signals, which eradiating from the integrins are transmitted via different yet interconnecting pathways and elicit various cell functions, such as morphological changes, adhesion, migration and gene activation. Any of these functions takes part in the metastatic cascade of tumor progression, such as epithelial-to-mesenchymal transition of carcinoma cells, tumor cell contact with the basement membrane, invasion into neighboring tissues as well as production and activation of ECM-degrading MMPs. Besides their direct involvement in tumor progression as cell surface molecules on tumor cells, integrins in normal cells surrounding a tumor, e.g. endothelial cells, can also determine various cancer characteristics, such as tumor-induced neoangiogenesis and immune resistance. Hence, integrins are relevant pharmacological targets in tumor biology. Spurred by the recent success to generate pharmaceutical mimetics of RGD-dependent integrins and by the integrin's easy accessibility on the cell surface, the hope is rising that also RGD-independent integrins, such as the collagen- and laminin-binding integrins, can be pharmacologically manipulated to fight integrin-dependent functions of cancer cells, which are necessary and at least partially specific for their proliferation and progression
Keywords: tumorigenesis